2019
DOI: 10.1002/ecy.2749
|View full text |Cite
|
Sign up to set email alerts
|

Plant species dominance increases pollination complementarity and plant reproductive function

Abstract: Worldwide, anthropogenic change is causing biodiversity loss, disrupting many critical ecosystem functions. Most studies investigating the relationship between biodiversity and ecosystem functioning focus on species richness, predominantly within the context of productivity‐related functions. Consequently, there is limited understanding of how other biodiversity measures, such as species evenness (the distribution of abundance among species), affect complex multitrophic functions such as pollination. We explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 90 publications
(167 reference statements)
2
15
0
Order By: Relevance
“…This conclusion was corroborated by the increased seed set of high-dependence species in ungrazed meadows. Stavert et al (2019) experimentally showed that the complementarity in pollinator use among plant species increased seed production of plants. Therefore, the higher visitation rate to high-dependence plants and specificity of pollinators in the ungrazed meadows appeared to improve plant reproductive performance.…”
mentioning
confidence: 99%
“…This conclusion was corroborated by the increased seed set of high-dependence species in ungrazed meadows. Stavert et al (2019) experimentally showed that the complementarity in pollinator use among plant species increased seed production of plants. Therefore, the higher visitation rate to high-dependence plants and specificity of pollinators in the ungrazed meadows appeared to improve plant reproductive performance.…”
mentioning
confidence: 99%
“…Unlike G. chungtienensis , there was no evidence of a change in the number of pollen grains deposited on A. ruprestris flowers along the Euphorbia dominance gradient. This lack of change suggests that although total visitation of this species might be reduced in high Euphorbia dominant communities, pollen deposition is maintained by specialist pollinators which show higher flower constancy (Stavert et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Ratzke et al, 2020;Ushio, 2020;Wootton & Emmerson, 2005). For example, complementarity among species causes positive relationships such as between plant diversity and productivity or between pollinators and pollination (Kunz et al, 2019;Stavert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%